2004
DOI: 10.1007/s00468-003-0286-7
|View full text |Cite
|
Sign up to set email alerts
|

Xylem embolism and stomatal regulation in two rubber clones ( Hevea brasiliensis Muell. Arg.)

Abstract: Vulnerability to water-stress-induced embolism of stems, petioles, and leaf midribs was evaluated for two rubber clones (RRIM600 and RRIT251). The xylem conduits were relatively vulnerable to cavitation with 50% of embolism measured for xylem pressures between -1 and -2 MPa. This feature can be related to the tropicalhumid origin of the species. A distinct basipetal gradient of vulnerability was found, leaf midribs being the least vulnerable. Substantial variation in vulnerability to cavitation was found betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…It was hypothesised that a higher susceptibility to cavitation/embolism in the drought-sensitive clone result from a steeper decline in hydraulic conductance under drought conditions (Costa e Silva et al 2004). Clonal differences in hydraulic architecture have also been reported by previous studies (Vander Willigen and Pammenter 1998;Sangsing et al 2004).…”
Section: Discussionsupporting
confidence: 59%
“…It was hypothesised that a higher susceptibility to cavitation/embolism in the drought-sensitive clone result from a steeper decline in hydraulic conductance under drought conditions (Costa e Silva et al 2004). Clonal differences in hydraulic architecture have also been reported by previous studies (Vander Willigen and Pammenter 1998;Sangsing et al 2004).…”
Section: Discussionsupporting
confidence: 59%
“…To moderate the reduced leaf water potential and to avoid cavitation (Sperry et al 1993, Hubbard et al 1999, Sangsing et al 2004, stomatal conductance (g s ) is reduced. This limits carbon uptake and prevents water loss through transpiration (Hubbard et al 1999, Bond et al 2007, which explains the midday depression in the gas exchange rate (Koike et al 2001a, Grassi et al 2005.…”
Section: --mentioning
confidence: 99%
“…Thus, it is logical to expect that current rubber plantations in northeastern Thailand and central Cambodia must cope with strong seasonal water stress via the SPAC context, such as limiting tree water use by regulating stomatal behavior in response to soil moisture deficit, and compensating for lack of water near the surface during the dry season by exploiting deeper soil water. Further, it is important to note that a previous study (Sangsing et al, 2004) found different rubber clones exhibit varying degrees of adaptability to water stress, thus it would be expected that water use efficiency and risk of hydraulic fracture vary with clone type in a particular climate.…”
Section: Introductionmentioning
confidence: 98%